Systemic factors of projected financial potential of business entities - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна (My University, 2016)
EN: The main prerequisite of forecasting the level of financial potential is the knowledge of financial activity of business entities. This becomes possible if the material basis of the financial potential is identified in the form of an isolated system, which consists of a definite number of elements and has distinct properties of financial resources. The algorithm of forecasting the level of financial potential is developed through a sequence of phases of cost management of financial flows of 2,276 agricultural business entities located in Zaporizhzhya, Kherson and Mykolaiv regions that specialise in crop production in 2009-2015. The implementation of the algorithm is performed by means of forecasting the movement of financial flows, speed and changes in the cost of formation of financial flows, as well as by determining the real cost of cash flows based on inflation losses, depreciation, exchange rate fluctuations in the internal and external markets. It was established that the accumulated liquid financial resources and a continuous increase in cash receipts of the studied enterprises can be considered satisfactory, however the nominal quantity of financial flows with regard to their strength and likelihood of change in their value over time indicates a gradual deterioration of fiscal balance and a slowdown in the formation of investment income of business entities. It has been determined that the synchronisation of cash inflows and outflows accelerates the flow of financial resources, capitalises the temporarily free balance and makes it possible to conduct investment operations with regard to possible terms of return and risks of financial activities of business entities. The author has proposed an appropriate model which statistical quality, value and reliability is sufficient for the use in forecasting the level of financial potential of agricultural entities. UK: Головною передумовою прогнозування рівня фінансового потенціалу як об’єкта є пізнання фінансової діяльності суб’єктів господарювання. Це стає можливим, якщо виокремити матеріальну основу фінансового потенціалу у вигляді визначеної ізольованої системи, яка складається із кінцевого числа елементів і має чітко виражені властивості фінансових ресурсів. Розроблено алгоритм прогнозування рівня фінансового потенціалу через послідовність етапів управління вартістю фінансових потоків суб’єктів господарювання, які розташовані на території Запорізької, Херсонської та Миколаївської областей та спеціалізуються на виробництві продукції рослинництва. Реалізація алгоритму здійснюється шляхом: прогнозування руху фінансових потоків; швидкості та зміни вартості джерел формування фінансових потоків; визначення реальної вартості фінансових потоків з урахуванням інфляційних втрат, коливань валютних курсів. Встановлено, що накопичені ліквідні фінансові ресурси та тривале зростання грошових надходжень досліджуваних підприємств мають задовільне значення, але номінальний обсяг фінансового потоку з урахуванням сили та ймовірності зміни його вартості у часі свідчить про поступове погіршення фінансової рівноваги та уповільнення формування інвестиційного доходу. Визначено, що синхронізація вхідних та вихідних фінансових потоків прискорює процес надходження фінансових ресурсів, капіталізує тимчасово вільні їх залишки, дозволяє здійснювати операції з інвестування, враховуючи можливі терміни доходності та ризики фінансової діяльності суб’єктів господарювання. Запропонована автором модель є адекватною. Її статистична якість, значущість і достовірність достатні для використання у прогнозуванні рівня фінансового потенціалу суб’єктів господарювання аграрного напряму. RU: Основной предпосылкой прогнозирования уровня финансового потенциала как объекта является познание финансовой деятельности субъектов хозяйствования. Это становится возможным, если выделить материальную основу финансового потенциала в виде определенной изолированной системы, которая состоит из конечного числа элементов и имеет четко выраженные свойства финансовых ресурсов. Разработан алгоритм прогнозирования уровня финансового потенциала через последовательность этапов управления стоимостью финансовых потоков субъектов хозяйствования, которые расположены на территории Запорожской, Херсонской и Николаевской областей и специализируются на производстве продукции растениеводства. Реализация алгоритма осуществляется путем: прогнозирования движения финансовых потоков; скорости и изменения стоимости источников формирования финансовых потоков; определения реальной стоимости финансовых потоков с учетом инфляционных потерь, колебаний валютных курсов. Установлено, что накопленные ликвидные финансовые ресурсы и продолжительный рост денежных поступлений на исследуемых предприятиях имеют позитивное значение, однако номинальный объем финансового потока с учетом силы и возможности изменения его стоимости во времени свидетельствует о постепенном ухудшении финансового равновесия и замедлении формирования инвестиционного дохода. Определено, что синхронизация входных и выходных финансовых потоков ускоряет поступлениe финансовых ресурсов, капитализирует временно свободные остатки, позволяет осуществлять операции по инвестированию, учитывая возможные сроки доходности и риски финансовой деятельности субъектов хозяйствования. Предложенная автором модель является адекватной. Её статистическое качество, значимость и достоверность достаточны для применения в прогнозировании уровня финансового потенциала субъектов хозяйствования аграрного направления.
Системні фактори прогнозованого рівня фінансового потенціалу суб’єктів господарювання
Системные факторы прогнозируемого уровня финансового потенциала субъектов хозяйствования
Keywords: Financial Resources; Financial Potential; Financial Projecting; Cost Management of Financial Flows; Business Entities; фінансові ресурси; фінансовий потенціал; фінансове прогнозування; управління вартістю фінансових потоків; суб’єкти господарювання; финансовые ресурсы; финансовый потенциал; финансовое прогнозирование; управление стоимостью финансовых потоков; субъекты хозяйствования